Evaluating effect of cutting depths on regrowth of invasive cattails (Typha angustifolia) - Moorberg, Colby J.; Travis, Steven E.; Ahlers, Adam A. (My University, 2022)
Cattail (Typha spp.) expansions into wetland ecosystems can reduce open-water habitats and negatively affect both native flora and fauna diversity. Cattail removal is needed to maintain wetland habitat quality; however, removal is often non-permanent requiring repeated treatments to retard reestablishment. Cutting cattails with mechanical harvesters is a common management technique; however, it is unclear what cutting depths are optimal. We conducted a controlled, replicated experiment at Cheyenne Bottoms Wildlife Area near Great Bend, Kansas, USA during 2017-2018 to address this question. We hypothesized that cattails cut below water would have reduced gas exchange capabilities due to flooded aerenchyma resulting in greater mortality. We conducted genetic testing to determine the species of cattail and determined the cattails to be narrowleaf cattail (Typha angustifolia), which is considered an invasive species in Kansas. Within this stand of cattail, we established a randomized complete block design experiment with four blocks, and three clipping treatments in July 2017. The clipping treatments included a control (no cattails were clipped), an above-water treatment (cattails cut 15 cm above the surface of the water) and a below-water treatment (cattails cut 15 cm below the water surface water). We quantified emergent stem densities in each plot in September 2017 to assess the effectiveness of simulated management actions. We predicted lower emergent stem densities in below-water cutting treatment blocks compared to both the control and above-water cutting treatment blocks. Mean stem densities were greatest in the control (113.0±10.7 stems). Clipping the cattails resulted in significantly fewer stem counts in both the above-water cutting treatment (44.1±10.7, p=0.0032) and in the below-water cutting treatment blocks (11.1±12.5, p=0.0004). The BW treatment had fewer stems than the AW treatment, though this difference was not significant (p=0.0789) at an alpha of 0.05. Our experimental setup was inadvertently destroyed with herbicides in 2019 preventing further treatment comparisons. This is the first known genetic-level confirmation of narrowleaf cattail at Cheyenne Bottoms Wildlife Area, which is a Ramsar Wetland of International Importance. Our results suggest that management efforts focused on cutting cattails below water can reduce cattail growth.
"Moorberg, C., Travis ,S., & Ahlers, A. (2022)Evaluating effect of cutting depths on regrowth of invasive cattails (Typha angustifolia). Preprint” supersedes "Moorberg, C. & Ahlers, A. (2020). An experimental evaluation of cattail (Typha spp.) cutting depths on subsequent regrowth. Preprint."
Keywords: Cheyenne Bottoms; KANSAS; Typha latifolia; Cattail; Wetland management; Ramsar